River Algae - Necchi JR, Orlando (Springer International Publishing : Imprint: Springer, 2016)
The content is focused on benthic communities showing how they play an in important role in the river ecosystems. Provides also information on taxonomy of river-inhabiting algal groups, including phylogeny, distribution, collection, preservation and description of the most representative genera of algae in river benthic algal communities. The book also approaches the ecology of river algae not to mention the ecological factors influencing abundance, distribution and diversity of river benthic algal communities and their use as bio-indicators, providing an up-to-date information on taxonomy, ecology, methodology and uses, and a great source of research to everyone interested in freshwater algae, limnology, water quality assessment and biodiversity in river ecosystems. .